Diagn Interv Radiol 2022
DOI: 10.5152/dir.2022.211100
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate pulmonary subsolid nodules in patients with no history of cancer: growing prediction, CT pattern, and pathological diagnosis

Abstract: We aimed to evaluate and compare the growth patterns among pathological types of indeterminate subsolid nodules in patients without a history of cancer as observed on computed tomography (CT). METHODSThis retrospective study included 77 consecutive patients with 80 indeterminate subsolid nodules on unenhanced thin-section CT. Subsolid nodules were classified into 2 growth pattern groups based on volume: growth (n = 35) and non-growth (n = 42). According to the pathological diagnosis, subsolid nodules were furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…28 The likelihood of pathological invasiveness increases with lesion size, consolidation part, and solid proportion. 29,30 During follow-up, the solid components of numerous lung nodules grew, raising the possibility that the nodules will turn malignant. Following a puncture biopsy, pathology revealed them as early-stage lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The likelihood of pathological invasiveness increases with lesion size, consolidation part, and solid proportion. 29,30 During follow-up, the solid components of numerous lung nodules grew, raising the possibility that the nodules will turn malignant. Following a puncture biopsy, pathology revealed them as early-stage lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ground‐glass opacity components represent lepidic growth and the solid components are related to invasion in lung cancer 28 . The likelihood of pathological invasiveness increases with lesion size, consolidation part, and solid proportion 29,30 . During follow‐up, the solid components of numerous lung nodules grew, raising the possibility that the nodules will turn malignant.…”
Section: Discussionmentioning
confidence: 99%
“…However, they have specified only 77 pathological diagnoses, including 29 adenocarcinomas in situ , 29 minimally invasive adenocarcinomas, 18 invasive adenocarcinomas, and one atypical adenomatous hyperplasia. 1 There is a discrepancy in the number of resected and histopathologically reported nodules in the study.…”
mentioning
confidence: 83%
“…I read with interest the original article entitled “Indeterminate pulmonary subsolid nodules in patients with no history of cancer: growing prediction, CT pattern, and pathological diagnosis” by Guo et al 1 In this retrospective study, the authors assessed the growth patterns of indeterminate subsolid pulmonary nodules on computed tomography in patients without a history of malignancy. The authors reported that the risk of pulmonary subsolid nodule growth increases by 4% each year in patients without a history of malignancy.…”
mentioning
confidence: 99%
“…15 The clinicopathologic behaviors of rPSNs appear to be worse than those of hGGNs. 16 However, previous studies on the natural process of SSNs mainly compared pGGNs and PSNs separated by the LW, 1,[17][18][19] and did not provide enough information on the natural history with regard to the solid component on different window settings. This study aims to investigate the natural history and clinicopathological aspects of pGGNs, hGGNs, and rPSNs with long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%